2014
DOI: 10.1016/j.celrep.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced TLR-MYD88 Signaling Stimulates Autoinflammation in SH3BP2 Cherubism Mice and Defines the Etiology of Cherubism

Abstract: Summary Cherubism is caused by mutations in SH3BP2. Studies of cherubism mice showed that TNF-α-dependent autoinflammation is a major cause for the disorder, but failed to explain why human cherubism lesions are restricted to jaws and regress after puberty. We demonstrate that the inflammation in cherubism mice is MYD88-dependent and is rescued in the absence of TLR2 and TLR4. However, germ-free cherubism mice also develop inflammation. Mutant macrophages are hyper-responsive to PAMPs (pathogen-associated mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 54 publications
4
88
0
Order By: Relevance
“…Strikingly, depleting the commensal microbiota with oral antibiotic treatment did not decrease the inflammation in homozygous cherubic mice (Supplemental Figure 9). However, in agreement with a recent study (20), crossing Sh3bp2 KI/KI mice with Myd88 KO/KO mice reduced serum TNF-α to WT levels, demonstrating the involvement of TLR signaling in autoinflammation of homozygous cherubic mice ( Figure 3F). Most importantly, LPSstimulated heterozygous cherubic BMM displayed enhanced signaling activities compared with WT macrophages (Figure 3, C and D), and heterozygous cherubic mice (Sh3bp2…”
Section: Wt/kisupporting
confidence: 79%
“…Strikingly, depleting the commensal microbiota with oral antibiotic treatment did not decrease the inflammation in homozygous cherubic mice (Supplemental Figure 9). However, in agreement with a recent study (20), crossing Sh3bp2 KI/KI mice with Myd88 KO/KO mice reduced serum TNF-α to WT levels, demonstrating the involvement of TLR signaling in autoinflammation of homozygous cherubic mice ( Figure 3F). Most importantly, LPSstimulated heterozygous cherubic BMM displayed enhanced signaling activities compared with WT macrophages (Figure 3, C and D), and heterozygous cherubic mice (Sh3bp2…”
Section: Wt/kisupporting
confidence: 79%
“…Corrective surgery by curettage with or without bone grafting is sometimes performed for extensively enlarged jaws [44]. Generally, such surgical intervention is considered only in severe cases and most of the surgical interventions are performed after puberty when cherubic lesions may become inactive, although mechanisms of the age-dependent phenotype regression in human cherubism patients, but not in cherubism mice, remain to be further elucidated [3]. Age-associated change in immune responses by TLRs [45, 46] might be a cause of the regression [3].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BMT was effective even in treating fully inflamed Sh3bp2 KI/KI mice, which were not ameliorated with anti-TNF-α therapy in mice and humans [20, 21], suggesting that wild-type BMT also corrected inflammatory cytokine levels other than TNF-α. We have previously reported that cherubism is a hematopoietic disorder of myeloid lineage cells caused by hyperactive macrophages and osteoclasts [3, 18, 22, 52]. Therefore, we assume that replacement of the mutant macrophages and osteoclasts with those carrying wild-type SH3BP2 is a main cause of the improved symptoms in Sh3bp2 KI/KI mice, which resulted in the comprehensive reconstitution of the expression profile of inflammatory cytokines and osteoclast-mediated bone resorption activity in Sh3bp2 KI/KI recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…106 TLR stimulation, either by PAMPs or DAMPs, is generally thought to have a central role in the pathogenesis of autoinflammation. 107 Thus, targeting factors along this axis might represent an approach with broad therapeutic utility if, in the case of TLR-targeting, residual TLR functions are retained for host-defence. Alternatively, direct targeting of DAMPs could offer the advantage of causing few adverse effects, as these molecules are released only after cell stress or damage.…”
Section: Pamps Damps and Tlrsmentioning
confidence: 99%